Incisional pyoderma gangrenosum after caesarean section: Two case reports - Tsuyoshi Murata; Hyo Kyozuka; Toma Fukuda; Tsuyoshi Hiraiwa; Akiko Yamaguchi; Keiya Fujimori (Elsevier, 2019)
Introduction: Pyoderma gangrenosum (PG) in pregnant women is rare and resembles surgical site infection (SSI). Here we present two cases of PG after caesarean section. Case 1: A 29-year-old woman, who had a history of recurrent wound dehiscence after surgery, exhibited wound ulceration and exudate 6 days after caesarean section. Antibiotics were ineffective and multiple wound cultures were negative. Skin biopsy indicated PG and oral steroid administration resulted in wound improvement. Case 2: A 27-year-old woman, who had a history of PG, exhibited wound ulceration and exudate 5 days after caesarean section. The lesion developed despite antibiotic administration, and multiple wound cultures were negative. Skin biopsy indicated PG and the wound improved after oral steroid administration. Discussion: Definitive diagnosis of PG is essential because its treatment differs from that of SSI. PG after caesarean section can be misdiagnosed as SSI, even when there is a history of wound dehiscence or PG. Keywords: Pyoderma gangrenosum, Caesarean section